From CSR to Brand Activism: Exploring Emerging Trends in Indonesia's Marketing Landscape - Muhamad Yusup; Hamdan Hidayatulloh (Indonesian Research of Sustainability Management, Business, & Administration (IRHAMNA), 2025)
The growing demand for brands to engage in sociopolitical issues has shifted the corporate focus from traditional Corporate Social Responsibility (CSR) to brand activism. While this transformation is well-documented in Western contexts, its trajectory in Indonesia remains underexplored. This study aims to investigate how brand activism has emerged within the Indonesian marketing landscape by examining its relationship with CSR, social media, brand equity, and authenticity. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, this study analyzes 73 peer-reviewed articles published between 2010 and 2025. The results show a clear evolution from philanthropic CSR to values-driven brand activism, catalyzed by digitally empowered consumers and amplified by social media platforms. Authenticity is identified as the most critical determinant of effective activism, as consumers increasingly evaluate the consistency between brand messaging and internal practices. While well-aligned activism strengthens brand equity through enhanced trust and emotional engagement, superficial or opportunistic efforts risk reputational damage. In the Indonesian context, cultural sensitivity and issue localization are crucial for brand credibility. This study contributes to both theoretical and practical understanding by situating brand activism within a Southeast Asian context and offering strategic insights for marketers aiming to build trust and differentiation in socially conscious markets. Future research is encouraged to incorporate empirical methods and explore employee perspectives on brand authenticity.